Urgensi Pendidikan Bisnis Sejak Dini: Analisis Ekonomi Syariah - M. Mulyakhan (Al-Widad, 2022)
Ideally, early business education should shape a generation with strong economic understanding, financial independence, and business ethics aligned with Islamic values. However, in reality, formal education still places greater emphasis on cognitive aspects and technical skills, while sharia-based business education has not been systematically integrated from an early age. This condition results in low levels of sharia business literacy and weak internalization of moral values in the economic practices of young generations. This study aims to analyze the urgency of early business education from the perspective of Islamic economics and to examine its role in shaping character and economic independence. The methodology employed is library research using a qualitative approach with descriptive-analytical analysis of relevant academic literature. The findings indicate that sharia-based early business education plays a strategic role in instilling values of honesty, justice, responsibility, and balance in economic activities. Such education not only enhances business literacy but also shapes an Islamic economic mindset and ethical behavior in a sustainable manner. Therefore, the integration of sharia-based business education from an early age is an urgent necessity for developing ethical and competitive human resources